Encouraging Children’s Environmental Awareness through Pictorial Children’s Story Sea Change - Yanuaresti Kusuma Wardhani; Yudhanita Pertiwi; Hardono Hardono (Jurnal Sinestesia, 2023)
Rising sea level as one of the effects of climate change may probably destroy the coastal area. This nature phenomenon is explained in a pictorial children's storybook entitled Sea Change. The story tells about rising sea level in Fiji, and it is suitable to the reality occurring in Fiji. Rising sea level reaches the land by the sea, hence the people living there must be relocated. Sea Changes is analyzed using ecocritical approach and semiotic theory. This study aims to reveal the meaning of visual appearance which goes to the values containing in the story. The analysis reveals four ecocritical elements by Scott Slovic, these are where the humans are, where the humans live, how the humans treat the environment, and how humans treat other humans. The four questions are answered using semiotic theory by Charles Sanders Peirce. The method used in this study is a qualitative method with descriptive analysis, which emphasizes the process of semiosis with the meaning of the relationship between signs or representamen in the pictorial book and the values for children. The results of the study are that Sea Change gives some value for children, these are about where humans properly live, and how humans properly treat the environment and other humans.